Measuring jury diversity in the court of public opinion - Tanaka, B. (Journal of ethnicity in criminal justice, 2025)
Do jury pools reflect the community from which they are drawn, and how can one be certain? Inspired by the growing body of diversity science literature, this study explores some of the complex dimensions involved in measures of juror heterogeneity. Using survey data from a sample of nearly 38,000 summonsed jurors in Washington State, this research explores the discordance between jurors’ self-identified race/ethnicity and their perceptions of how others ascribe them, using Census Bureau classifications. Findings indicate that the incongruence between one’s personal identification and external categorization may account for the observed variability in juror representation across different stages of the juror selection process. Specifically, a significant portion of respondents who self-identified as non-White reported feeling that they were perceived as White by others. We speculate that instances of racial contestation may inadvertently contribute to the exclusion of non-White individuals on the basis of one’s phenotypical proximity to Whiteness. Potential implications for criminal justice reform efforts and future research directions are discussed.